PENINGKATAN MOTIVASI DAN HASIL BELAJAR PADA MATERI CIRI-CIRI MAKHLUK HIDUP MELALUI PEMBELAJARAN SNOWBALL THROWING - Sembiring, Riniwati Br. (Unversitas Katolik Santo Thomas, 2022)
This study aims to find out how to improve student learning outcomes who are taught using the Snowball Throwing learning model on the material characteristics of living things for class VII SMP Advent 3 Medan in the 2020/2021 academic year. The population and sample in this study were all seventh graders of SMP Advent 3 Medan, totaling 22 people, consisting of 15 male students and 7 female students. The instrument used after testing the research hypothesis instrument was tested using the T test. These results indicate: 1. Students who are taught using the Snowball Throwing `learning model get better results, with the average value of the latest learning outcomes is 85.00 and students who get a score of 70 as much as 100%